Chances and Risks of a new Residency Program for Orthopedics and Trauma Surgery - Merschin, David; Muenzberg, Matthias; Perl, Mario (Zeitschrift für Orthopädie und Unfallchirurgie, 2013)
Background: The residency program for a specialist in orthopedics and trauma surgery is facing fundamental changes based on an initiative originating from the working group medical training" of the German Medical Association (GMA). A survey indicated that 50% of all trainees are dissatisfied with their current situation. It appears important to integrate the ideas and wishes of current orthopedic residents in a novel training concept. To assess this a survey was performed by the Young Forum of the German Society for Orthopedics und Trauma Surgery.Material and Methods: The internet-based short survey was conducted in January 2013 among members of the professional societies (DGU, DGOU and DGOOC). 408 physicians participated.Results: The majority of the participating physicians is interested in a career in orthopedics and trauma surgery with primarily operative contents. Accordingly the majority (62%, n=253) voted against a reduction of numbers of surgical interventions with 86% (n=351) confirming the necessity that these operations must be carried out by the trainee himself.Conclusion: The upcoming changes in residency program for orthopedics and trauma surgery offer the oportunity for a well structured and practical oriented residency program. It could be a furhter step in increasing satisfaction in this profession.
Keywords: residency program; orthopedics and trauma surgery; Youth Forum of the DGOU